El derecho constitucional a la libertad ambulatoria y el control difuso por el tribunal penal de Chimborazo - Ecuador - Ayme Azogue, José Alfredo (2024)
The Inter-American Court of Human Rights urges the States Parties to the Convention to apply through the authorities the diffuse control of conventionality, a figure created by that international judicial body as a procedural mechanism for the protection of human rights; however, the violation of the constitutional right to freedom of movement is presented as an investigation problem, due to the lack of application of the procedural guarantee of diffuse control of conventionality by the Court of Criminal Guarantees of Chimborazo - Ecuador, when issuing convictions in the crime of fraud, in the first quarter of 2022; The proposed objective is to carry out a critical-legal analysis on the constitutional right to freedom of movement, due to the lack of application of the procedural guarantee of diffuse control of conventionality by the Court of Criminal Guarantees of Chimborazo - Ecuador, when issuing convictions in the crime of fraud, in the first quarter of 2022, to contribute to respecf for this right. Research methods, at the theoretical and empirical levels, with their respective instruments, have been used to study the object. As a result, it is a treaty duty, of general scope, that the domestic laws of States contain norms that allow for the effective enjoyment of each and every one of the rights proclaimed as human rights. It is concluded that it is necessary for Ecuadorian courts to apply the diffuse control of conventionality in order to protect the human rights of those prosecuted in crimes such as fraud.